Comparative public policy - Dodds, Anneliese (Palgrave Macmillan, 2013)
"A major new introduction to the comparative study of public policy. It examines the policy process in a wide range of policy areas and countries and considers the challenges of transferring policies from one society to another."--Publisher's website.